A similar material for siliceous cemented structural surface interlayer and its preparation method

A siliceous cemented structural surface interlayer material, combining specific components and blending agents, addresses the dynamic property gap in hard structural surfaces, achieving similar tensile and shear characteristics and density, enhancing research on hard structural surfaces.

CN115893971BActive Publication Date: 2024-12-20GUANGXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211376522.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-04
Publication Date
2024-12-20
Estimated Expiration
2042-11-04

AI Technical Summary

Technical Problem

Current research on similar materials for hard structural surfaces with high cementation strength and thin thickness lacks consideration of dynamic properties, leading to inadequate representation of shear and tensile characteristics, and there is a scarcity of systematic studies on siliceous cemented structural surface interlayers.

Method used

A siliceous cemented structural surface interlayer similar material composed of quartz, feldspar, mica, chlorite, calcium carbonate powder, gypsum, sodium silicate, water, borax, water reducer, and graphene oxide, designed using a uniform design method to achieve similarity in tensile strength, shear characteristics, perturbation dynamics, and disturbance damage characteristics, with specific ratios and blending processes.

Benefits of technology

The material exhibits similar tensile and shear properties to the original rock, with improved density and adaptability to physical and mechanical characteristics, using widely available and non-toxic materials, ensuring consistency with the original rock's properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115893971B_ABST
    Figure CN115893971B_ABST
Patent Text Reader

Abstract

Similar materials for siliceous cemented structural surface interlayer and preparation method thereof belong to the technical field of similar materials, including aggregates: quartz, feldspar, mica, chlorite, calcium carbonate powder; curing agent: gypsum, sodium silicate; conditioning agent: water, borax, water reducer and graphene oxide. The mass ratio of quartz to the feldspar is 2-0.5; the sum of the mass of mica and chlorite accounts for 0%-15% of the total mass of aggregate; calcium carbonate powder accounts for 0-5% of the total mass of aggregate; the specific gradation and content of each aggregate are determined by the mineral gradation and content of the original rock structural surface interlayer; the amount of conditioning agent is fixed at 30% of the mass of the curing agent, and the ratio of graphene oxide to the curing agent is 0-0.06%. The mass ratio of aggregate to curing agent is 0.5-2; the mass ratio of gypsum to sodium silicate of the curing agent is 0.5-2. The present invention realizes the development of materials with similar tensile strength, shear strength and disturbance damage characteristics of original rock structural surfaces, and solves the problem of material sources for the study of hard structural surfaces in deep engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of similar materials, and in particular to a siliceous cemented structural surface interlayer similar material and a preparation method thereof. Background Art

[0002] Natural rock masses often have obvious geological relics, such as unconformity surfaces, folds, faults, joints, etc. The existence of these geological structures causes the discontinuity of the rock mass medium, so these interfaces are called structural surfaces. It is the existence of structural surfaces that affects the mechanical characteristics of the rock mass, causing the mechanical discontinuity and anisotropy of the rock mass. A complete rock mass structural surface includes the upper and lower plates with structural surfaces and the interlayer between the upper and lower plates. The structural surfaces commonly seen in open-pit slopes, road cuts and other projects are often filled with rock debris, silt, weathered gravel, etc. This type of structural surface generally has less cementation or no cementation ability, which we call a weak structural surface. In the surrounding rock mass of deep engineering, the structural surface often appears with the characteristics of thin cementation thickness and high cementation strength, which is different from the structural surface in the conventional sense, and is called a hard structural surface. At present, most scholars focus on the study of structural surfaces on weak structural surfaces, while the study of this type of hard structural surface with high cementation strength and thin thickness is relatively scarce.

[0003] In view of the difficulty of on-site sampling of structural surfaces, the high economic cost and certain danger, most scholars use similar materials to prepare structural surface samples. Most scholars have carried out research on weak structural surfaces. They have mostly conducted certain similar material research on the upper and lower plates of the structural surface. The main factors considered are the morphological characteristics of the structural surface itself, the filling thickness, and the filling materials. For the similar material research of the structural surface filling layer itself, they have made choices. They mostly use silt, rock fragments and other filling materials commonly found in weak structural surfaces as structural surface filling materials, and there is still a lack of systematic research on the deep siliceous cemented structural surface interlayer.

[0004] The characteristic of hard structural surface, which is different from weak structural surface, is that it has the characteristics of thin bonding thickness and high bonding strength, which determines that the bonding layer of hard structural surface has a certain tensile strength; the shear failure of hard structural surface is jointly dominated by the bonding force of the filling layer and the bite force of the upper and lower plate concave and convex characteristics. At present, the similarity criteria of similar rock-like materials generally only consider the similarity of the static physical and mechanical parameters of the prototype material, lacking the similarity of the perturbation dynamic properties of similar materials. The series of rock-like materials obtained by the traditional static similarity criteria can no longer meet the relevant research on the dynamic characteristics of hard structural surfaces. Based on this, the present invention combines the two most significant material characteristics of the hard structural surface interlayer bonding force and shear characteristics as design factors, and considers the similarity of similar materials in perturbation dynamic properties. Through the similarity of the four conditions of tensile strength, shear characteristics, perturbation dynamic properties and perturbation damage characteristics of similar materials, the similarity criteria of similar materials of siliceous cemented structural surface interlayer are obtained.

[0005] Based on the above, the present invention proposes a similar material for a siliceous cemented structural surface interlayer and a preparation method thereof to address the current gaps in research on similar materials for hard siliceous cemented structural surfaces interlayer and the shortcomings in research on hard structural surfaces. Summary of the invention

[0006] The invention provides a siliceous cemented structural surface interlayer similar material, which comprises the following components: aggregates: quartz, feldspar, mica, chlorite, calcium carbonate powder; curing agent: gypsum (2000 mesh), sodium silicate; and blending agent: water, borax, water reducer and graphene oxide.

[0007] The proportion of each component in the aggregate is as follows: the mass ratio of the quartz to the feldspar is 2 to 0.5; the sum of the masses of the mica and the chlorite accounts for 0% to 15% of the total mass of the aggregate; the calcium carbonate powder accounts for 0 to 5% of the total mass of the aggregate; the particle size gradation and content of each component of the specific aggregate are determined by the particle size distribution and mineral content distribution of the interlayer of the original rock structure surface.

[0008] The amount of the regulator is fixed at 30% of the mass of the curing agent, the water used for the regulator is pure water, the water reducer is a high-performance polycarboxylic acid water reducer, and the ratio of the mass of graphene oxide to the curing agent is 0 to 0.06%.

[0009] The mass ratio of the aggregate to the curing agent is 0.5-2; the mass ratio of the gypsum (2000 mesh) of the curing agent to the sodium silicate is 0.5-2.

[0010] The specific mix ratio of aggregate, curing agent and blending agent is determined according to the following steps:

[0011] (1) The similarity theory of similar materials for structural interlayers adopts the following similarity coefficient criteria:

[0012] a Similarity coefficient of tensile strength:

[0013] b Similarity coefficient of shear strength:

[0014] c Disturbance dynamics performance similarity coefficient:

[0015] d. Similar disturbance damage characteristics: The "S"-shaped damage evolution laws of the three stages of disturbance loading "deceleration, constant speed, and acceleration" for similar materials are similar.

[0016] Where: tM is the measured tensile strength of the original rock, σ tH is the actual tensile strength of similar interlayer materials; c M is the measured cohesion of the original rock, c H is the actual cohesion of similar interlayer materials; is the measured internal friction angle of the original rock, is the actual internal friction angle of similar interlayer materials; T M is the original rock disturbance failure period, T H is the disturbance failure cycle of similar interlayer materials.

[0017] (2) Based on the four factors of aggregate to curing agent ratio, gypsum to sodium silicate ratio, graphene oxide parameters, and diagenetic pressure, the uniform design method was used to design a 4-factor multi-level uniform test plan (see Table 1).

[0018] Table 1 Full-horizontal uniform design scheme for similar interlayer materials

[0019]

[0020] (3) According to the test plan, the material is made into a standard sample for Brazilian splitting and shearing test. The production process includes: weighing the material according to the test plan, mixing the aggregate and the consolidating agent, preparing the blending agent, pouring, continuously applying pressure and curing until the similar material is completely solidified. Brazilian splitting and shearing tests are carried out and regression curve analysis is performed on the uniform design test results. The best interlayer similar material mix ratio is obtained according to the similarity criterion in (1).

[0021] A method for preparing a similar material of a siliceous cemented structural surface interlayer adopts the above-mentioned similar material of a siliceous cemented structural surface interlayer, and specifically comprises the following steps:

[0022] Step 1: according to the final ratio of the interlayer similar materials and the particle size gradation of the original rock, quartz, feldspar, mica, chlorite and calcium carbonate powders of corresponding mass and particle size are weighed, and the powders are placed in a mixer and mixed and stirred evenly for later use;

[0023] Step 2: according to the final ratio of the interlayer similar materials, the corresponding water, water reducing agent and graphene oxide are weighed and placed in a beaker for mixing and stirring until the water reducing agent is completely dissolved, and the beaker is placed in an ultrasonic disperser for ultrasonic dispersion of the mixed solution to obtain a blending agent;

[0024] Step 3: Pour the prepared blending agent into the blender and mix for 3 minutes;

[0025] Step 4: Place the stirred interlayer-like material on the lower plate specimen of the structural surface, and spread the interlayer-like material evenly, further align the upper plate of the structural surface with the lower plate of the structural surface and place it on the interlayer-like material, and then seal the surrounding of the interlayer-like material;

[0026] Step 5: According to the molding pressure of the best ratio, the molding pressure is continuously applied to the similar interlayer material between the upper and lower plates of the structural surface, and the interlayer of the structural surface is cured while the molding pressure is applied, and the pressure curing time is 15 days;

[0027] Step 6: Remove the pressure, take out the complete structural test piece, and conduct a shear test.

[0028] The beneficial effects of the present invention are as follows:

[0029] 1. The tensile strength of the interlayer similar material of the structural surface proposed by the present invention is very close to that of the original rock structural surface, with a similarity ratio of about 1, and is tightly bonded to the upper and lower plates of the structural surface. The bite force between the two is greater than the tensile strength of the interlayer similar material, and the basic characteristics of tensile failure of the composite original siliceous structural surface are achieved;

[0030] 2. The structural surface interlayer similar material proposed in the present invention has the same shear characteristics as the original rock structural surface, which is of great significance to the study of the shear characteristics of the structural surface;

[0031] 3. The structural surface interlayer similar material and preparation method proposed in the present invention selects minerals with the same mineral composition and particle size distribution as the original rock in terms of aggregate selection, thereby ensuring the consistency of the basic physical and mechanical characteristic parameters of the similar material and the original rock; in terms of the preparation method, the diagenetic stress environment of the structural surface interlayer is taken into account, the density of the interlayer similar material is improved, and it is more in line with the common siliceous cemented structural surface characteristics;

[0032] 4. The present invention controls the strength, internal friction angle and cohesion of similar materials by combining two curing agents and regulating the content of graphene oxide in the blending agent. This method can adapt to the physical and mechanical characteristics of most siliceous cementing structural surfaces. Secondly, the raw materials of the present invention are widely available, easy to obtain, economical, affordable, non-toxic and harmless. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present application. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 A flow chart of a similar material of a siliceous cemented structural surface interlayer and a preparation method thereof according to a certain embodiment of the present invention;

[0035] Figure 2 A sample preparation flow chart of a silicon cemented structural surface interlayer similar material and a preparation method thereof according to a certain embodiment of the present invention;

[0036] Figure 3 A stress-strain curve of a similar material tensile test of a structural surface sandwich with an optimal ratio according to an embodiment of the present invention;

[0037] Figure 4 A shear displacement curve of a direct shear test of a similar material of a structural surface sandwich with an optimal ratio according to a certain embodiment of the present invention;

[0038] Figure 5 It is a schematic diagram of a method for preparing a similar material of a siliceous cemented structure surface interlayer according to a certain embodiment of the present invention;

[0039] Figure 6 The disturbance test strain curve of the structural surface interlayer similar material and the original rock with the best ratio in one embodiment of the present invention.

[0040] Among them, 1-structure surface upper plate specimen, 2-structure surface lower plate specimen, 3-structure surface interlayer similar material, 4-confining pressure plate. DETAILED DESCRIPTION

[0041] In order to deepen the understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used as detailed explanations of the present invention and cannot be used as limitations on the protection scope of the present invention.

[0042] The technical solution in the embodiment of the present invention is to solve the above technical problems, and the specific ideas are as follows:

[0043] The present invention provides a siliceous cemented structural surface interlayer similar material, wherein the structural surface interlayer similar material adopts quartz, feldspar, mica, chlorite, and calcium carbonate powder as aggregates; 2000 mesh high-strength gypsum and sodium silicate as curing agents; and a blending agent is prepared by mixing water, borax, a water reducer, and graphene oxide.

[0044] In one embodiment of the present invention, the prototype of the siliceous cemented structural surface is a chlorite siliceous cemented structural surface taken from a tunnel construction site, and its main mineral components and contents are: quartz 40%, feldspar 45%, mica + chlorite 10%, carbonate minerals 5%, and the particle size of each mineral is 15μm~30μm; according to indoor test tests, the physical and mechanical parameter indicators of the interlayer minerals of the structural surface are shown in Table 2.

[0045] Table 2 Physical and mechanical parameters of interlayer minerals in target structural surface

[0046]

[0047] According to the mineral information of the prototype structural surface, a similar material for the interlayer of a siliceous cemented structural surface in this embodiment is used as the aggregate: 4 parts of quartz sand (300 mesh-500 mesh), 4.5 parts of feldspar sand (300 mesh-500 mesh), 4 parts of muscovite (300 mesh-500 mesh), 6 parts of chlorite sand (300 mesh-500 mesh), and 5 parts of nano calcium carbonate (20nm).

[0048] The dosage of the regulator is fixed at 30% of the mass of the curing agent, the water used is laboratory pure water, the water reducer is a high-performance polycarboxylic acid water reducer, and the graphene oxide is a laboratory-grade single-layer graphene oxide, and the mass ratio of the graphene oxide to the curing agent is 0.01-0.06%.

[0049] The specific mix ratio of aggregate, curing agent and blending agent is determined according to the following steps:

[0050] (1) Based on the four factors of aggregate to curing agent ratio, gypsum to sodium silicate ratio, graphene oxide parameters, and diagenetic pressure, a uniform design method was used to design a uniform test plan with 4 factors and 6 levels (Table 3);

[0051] Table 3 Uniform design scheme for interlayer similar materials

[0052]

[0053] (2) According to the test plan, the material was made into Φ50mm×50mm Brazilian splitting specimens and 100mm×100mm×100mm shear specimens. The production process is as follows: Figure 2 , including: weighing materials, mixing aggregates and consolidating agents, preparing blending agents, pouring, continuously applying pressure and curing for 15 days according to the test plan, and the curing conditions are temperature 20°C and humidity 99%. Brazilian splitting and shearing tests are carried out and regression curve analysis is performed on the uniform design test results. According to the similarity criterion in step (1), the best interlayer similar material mix ratio is obtained, as shown in Table 4;

[0054] Table 4 Best ratio of similar materials

[0055]

[0056] According to the optimal ratio of similar materials in the structural surface interlayer, a Φ50mm×50mm Brazilian splitting specimen and a 100mm×100mm×100mm shearing specimen were made according to the above step (2). Brazilian splitting and direct shearing tests were carried out. Figure 3 and Figure 4 As shown: The experimental result curve of the best structural surface sandwich similar material, the physical and mechanical parameters of the structural surface sandwich similar material obtained according to the experimental data are shown in Table 5;

[0057] Table 5 Physical and mechanical parameters of similar materials for the best structural surface sandwich measured

[0058]

[0059] (3) The similarity coefficients are calculated from Table 5 as follows:

[0060] Similarity coefficient of tensile strength:

[0061]

[0062] Similarity coefficient of shear strength:

[0063]

[0064]

[0065] Similarity coefficient of perturbation dynamics performance:

[0066]

[0067] Where: tM is the measured tensile strength of the original rock, σ tH is the actual tensile strength of similar interlayer materials; c M is the measured cohesion of the original rock, c H is the actual cohesion of similar interlayer materials; is the measured internal friction angle of the original rock, is the actual internal friction angle of similar interlayer materials; T M is the original rock disturbance failure period, T H is the disturbance failure cycle of similar interlayer materials.

[0068] The disturbance damage characteristics are similar:

[0069] Disturbance test plan for similar materials and original rocks: First, load the similar materials and original rocks at a loading rate of 0.2MPa / s to the 0.9σ c (0.9 times of uniaxial compressive strength), and further apply a disturbance load with frequency f = 0.2HZ and amplitude A = 1MPa until failure; according to Figure 6 As shown in the figure, the disturbance damage cycle of similar materials in the best structural surface interlayer is 63, and the disturbance damage cycle of the original rock is 58. The disturbance damage characteristics of similar materials in the best structural surface interlayer and the original rock are basically the same. Both of them show three-stage disturbance damage characteristics on the strain-time relationship curve, which include deceleration damage stage, constant speed damage stage and acceleration damage stage.

[0070] The following is a method for preparing a similar material of a siliceous cemented structure surface interlayer according to an embodiment of the present invention. Figure 2 and Figure 5 As shown: A method for preparing a similar material of a siliceous cemented structure surface interlayer comprises the following steps:

[0071] Step 1: According to the final ratio of interlayer similar materials and the particle size gradation of the original rock, weigh quartz, feldspar, mica, chlorite and calcium carbonate powders of corresponding mass and particle size, place them in a blender and mix them for 5 minutes for later use.

[0072] Step 2: According to the optimal ratio of similar interlayer materials, corresponding water, water reducer and graphene oxide are weighed and placed in a beaker, mixed and stirred until the water reducer is completely dissolved, and the beaker is placed in an ultrasonic disperser for ultrasonic dispersion for 45 minutes to obtain a blending agent.

[0073] Step 3: Pour the prepared blending agent into the blender and mix for 3 minutes.

[0074] Step 4: place the stirred interlayer-like material 3 on the structural surface lower plate specimen 2, and spread the interlayer-like material 3 evenly, further align the structural surface upper plate 1 with the structural surface lower plate 2 and place it on the interlayer-like material 3, and then tighten the confining pressure plate 4 around the interlayer-like material 3 to prevent the interlayer-like material from being squeezed out when pressure is applied.

[0075] Step 5: Place the upper and lower plates of the structural surface together with similar interlayer materials in a force-applying frame to apply molding pressure of 10 MPa. Continue to apply pressure for 15 days and simultaneously perform curing. The curing conditions during the pressure application period are: temperature 20°C, humidity 99%.

[0076] Step 6: Remove the pressure, take out the complete structural test piece, and conduct a shear test.

Claims

1. A method for preparing similar materials for interlayers of siliceous cemented structural surfaces, characterized in that: The material includes the following components: aggregate: quartz, feldspar, mica, chlorite, calcium carbonate powder; Curing agent: gypsum with a particle size of 2000 mesh and sodium silicate; conditioning agent: water, borax, water reducing agent and graphene oxide; the proportion of each component in the aggregate: the mass ratio of the quartz to the feldspar is 2 to 0.5; the sum of the mass of the mica and chlorite accounts for 0% to 15% of the total mass of the aggregate; the calcium carbonate powder accounts for 0 to 5% of the total mass of the aggregate; the particle size gradation and content of each component of the specific aggregate are determined by the particle size distribution and mineral content of the interlayer of the original rock structure surface; The exact proportion of the aggregate, curing agent and blending agent is determined according to the following steps: (1) The similarity theory of similar materials for structural interlayers adopts the following similarity coefficient criteria: a Similarity coefficient of tensile strength: b Similarity coefficient of shear strength: c Disturbance dynamics performance similarity coefficient: d. The disturbance damage characteristics are similar: the "S"-shaped damage evolution rules of the three stages of disturbance "deceleration, constant speed, acceleration" are similar; Where: tM is the measured tensile strength of the original rock, σ tH is the actual tensile strength of similar interlayer materials; c M is the measured cohesion of the original rock, c H is the actual cohesion of similar interlayer materials; is the measured internal friction angle of the original rock, is the actual internal friction angle of similar interlayer materials; T M is the original rock disturbance failure period, T H is the disturbance failure cycle of similar materials in the interlayer; (2) Based on the four factors of aggregate to curing agent ratio, gypsum to sodium silicate ratio, graphene oxide dosage, and diagenetic pressure, a uniform design method was used to design a uniform test plan with four factors and multiple levels; (3) According to the test plan, the material is made into a standard sample for Brazilian splitting and shearing test, and the production process includes: weighing the material according to the test plan, mixing the aggregate and the consolidating agent, preparing the blending agent, pouring, continuously applying pressure and curing until the similar material is completely solidified; conducting Brazilian splitting and shearing tests and performing regression curve analysis on the uniform design test results, and obtaining the final interlayer similar material mix ratio according to the similarity criterion in (1); Using the above-mentioned siliceous cemented structural surface interlayer similar material, the specific preparation method includes the following steps: Step 1: according to the final ratio of the interlayer similar materials and the particle size gradation of the original rock, quartz, feldspar, mica, chlorite and calcium carbonate powders of corresponding mass and particle size are weighed, and the powders are placed in a mixer and mixed and stirred evenly for later use; Step 2: according to the final ratio of the interlayer similar materials, the corresponding water, water reducing agent and graphene oxide are weighed and placed in a beaker for mixing and stirring until the water reducing agent is completely dissolved, and the beaker is placed in an ultrasonic disperser for ultrasonic dispersion of the mixed solution to obtain a blending agent; Step 3: Pour the prepared blending agent into the blender and mix for 3 minutes; Step 4: Place the stirred interlayer-like material on the lower plate specimen of the structural surface, and spread the interlayer-like material evenly, further align the upper plate of the structural surface with the lower plate of the structural surface and place it on the interlayer-like material, and then seal the surrounding of the interlayer-like material; Step 5: According to the molding pressure of the best ratio, the molding pressure is continuously applied to the similar interlayer material between the upper and lower plates of the structural surface, and the interlayer of the structural surface is cured while the molding pressure is applied, and the pressure curing time is 15 days; Step 6: Remove the pressure, take out the complete structural test piece, and conduct a shear test.

2. A method for preparing a similar material for a siliceous cemented structural surface interlayer as described in claim 1, wherein the amount of the conditioning agent is fixed at 30% of the mass of the curing agent, the water used for the conditioning agent is pure water, the water reducer is a high-performance polycarboxylic acid water reducer, and the ratio of the mass of graphene oxide to the curing agent is 0 to 0.06%.

3. The method for preparing a similar material for a siliceous cemented structural surface interlayer as described in claim 1, wherein the mass ratio of the aggregate to the curing agent is 0.5 to 2; the mass ratio of the gypsum to the sodium silicate of the curing agent is 0.5 to 2.

Citation Information

Patent Citations

  • Sodium metasilicate cemented rock similar material and preparation method thereof

    CN104387012A

  • Geomechanical model test simulated deteriorated rock mass similar material and proportion determination method

    CN111892370A